Development of a driving cycle for Istanbul bus rapid transit based on real-world data using stratified sampling method - ERDAL, HASAN; KORKMAZ, HAYRİYE (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Environmental as well as financial issues forces to develop clean, efficient, and sustainable vehicles which constitutes an integral part of our daily life for urban transportation. Nevertheless, exhaust emissions of conventional internal combustion engine vehicles are the major source of global warming lead greenhouse effect. One solution for this issue is hybridization/electrification of the vehicles. One of the most important tools which can help to test performances of technical solutions systematically is driving cycles representing real driving conditions for vehicle emissions testing and estimation. When the history of the driving cycles was reviewed, it can be seen that there were big changes from constructing synthetically to real world cycles and from emission-focused cycles to emission, pollution and fuel consumption focused cycles. And now, a new application such as hybridization and/or electrification has been added to driving cycles. Main aim of this study is to create a practical driving cycle for Bus Rapid Transit (BRT) vehicles. To do this, characteristic driving parameters such as speed, distance, time, acceleration have been determined first. Data acquisition from conventional vehicles running on Istanbul route was performed and then data were analysed. A driving cycle was developed by using Proportional Stratified Sampling (PSS) technique. Comparison between constructed driving cycle and the real-world data show that difference is less than 10%. And so, it can be concluded that proposed driving cycle was acceptable.
Keywords: Driving cycle; Characteristic driving parameters; Public transportation; Bus rapid transit; Controller area network bus measurement; Data acquisition and analysing